(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: Reimbursement for inpatients in Switzerland differed among states until 2012. Some hospitals used diagnosis related groups (DRG) and others used fee-for-service (FFS). We compared length of hospital stay (LOS), patient satisfaction and quality of life between the two systems before a nation-wide implementation of DRG. METHODS: In a prospective, two-centre observational cohort study, we identified all patients with a main diagnosis of either community-acquired pneumonia, exacerbation of chronic pulmonary obstructive disease, acute heart failure or hip fracture from January to June 2011 and performed a systematic questionnaire survey 2–4 months after hospital discharge. RESULTS: Of 1,093 inpatients, 450 were included. Mean age was 71.1 (±SD 19.5) years (48% male). Patients in the FFS hospital were older (mean age 74.8 vs. 65.2 years; p <0.001) and suffered from more co-morbidities. Mean LOS was 9 days and shorter in the all-patient DRG (AP-DRG) hospital (unadjusted mean 8.2 vs. 9.5 days, p = 0.04). After multivariate adjustment, no significant difference in LOS was found (p = 0.24). More patients from the FFS hospital were re-hospitalised for any reason (35% vs. 17.5%; p = 0.01), re-admitted to acute-care institutions (11.7% vs. 5.2%; p = 0.014), not satisfied with the discharge process (15.3% vs. 9.7%; p = 0.02), showed problems with self-care (93.8% vs. 88%; p = 0.03) and usual activities (79.3% vs. 76%; p = 0.02). DISCUSSION: This study suggested that the AP-DRG hospital showed higher patient satisfaction regarding discharge, lower re-hospitalisation rates and shorter LOS partly explained by a lower burden of co-morbidities and disease severity. This study needs validation in a larger cohort of patients and at multiple time points.